(untitled) (International Seven Journal of Health Research, 2024)
Autism Spectrum Disorder (ASD) is a common neurodevelopmental disorder, marked by deficits in communication and social interaction and restricted and repetitive behavior patterns. With the expansion of information dissemination about autism and improvements in diagnostic methods, the prevalence of the disorder has increased considerably in recent decades. However, because autism has multiple facets and different presentations, diagnosis is still a challenge, especially in females, where there are singularities that further undermine suspicions, leading to underdiagnosis. Given this, there are multiple questions about the causes and implications of these factors in the diagnosis of autistic girls and women. Thus, the objective of this research is to verify the causal factors and clinical implications associated with the difficulty in diagnosing ASD in females. This is a narrative bibliographic review, in which research was carried out in established databases. In general, it is noted that the diagnosis of autism in girls and women can be impacted by genetic, developmental, psychological, social and cultural influences, involving factors such as subtlety of symptoms, capacity for social adaptability, lack of studies, failure to diagnostic methodologies and instruments, as well as stereotypes and prejudices. Understanding these elements is essential to broaden the perspective of girls and women with ASD, highlight their particularities and ensure that they receive early diagnosis and treatment.